Particle- and colloid-facilitated Pb transport in four historically contaminated soils - Speciation and effect of irrigation intensity. (September 2018) - Löv, Åsa; Cornelis, Geert; Larsbo, Mats; Persson, Ingmar; Sjöstedt, Carin; Gustafsson, Jon Petter; Boye, Kristin; Kleja, Dan B.
Abstract: Due to the low solubility of lead (Pb) in many soils, colloidal and particulate transport may have large effects on Pb leaching. However, the role of colloidal and particulate transport varies considerably between soils and the mechanisms controlling mobilisation are complex and poorly known. Furthermore, increased frequency of high-intensity rainfall events is expected in some parts of Europe and North America in response to climate change, which might increase the mobilisation of particles and colloids. In this work, we investigated transport of particulate (>0.45 μm), colloidal (10 kDa-0.45 μm) and truly dissolved (<10 kDa) Pb in an irrigation experiment on intact soil columns from four historically contaminated soils. We also investigated the effect of irrigation intensity (2–20 mm h −1 ) on Pb leaching in these fractions. The mechanism binding Pb on particles and colloids was evaluated by extended X-ray absorption fine structure (EXAFS) spectroscopy and geochemical modelling. A 10-fold increase in irrigation intensity brought about at most a three-fold change in leached particulate and colloidal Pb concentrations. In contrast, the fraction of leached Pb associated with particles and colloids varied by one order of magnitude between soils. Hence, the results suggest that it is more important to consider soil type than potential future increases in rainfall. For one soil with high concentrations of both arsenic (As) and Pb, geochemical modelling indicated that mimetite, Pb5 (AsO4 )3 Cl(s), was the major Pb species in the colloidal and particulate fractions. For the other three soils, EXAFS of Pb on isolated particles and colloids indicated that ferrihydrite was a major phase-sorbing Pb and this was supported by geochemical equilibrium modelling. Thus geochemical modelling can be used to indicate the speciation of Pb in particles and colloids leached in intact soils. Graphical abstract: Image 1 Highlights: Particle and colloidal transport has great potential impacts on Pb transport. Irrigation intensity has minor effects on Pb transport with particles and colloids. Pb adsorbed to Fe hydroxides is a major phase in particles and colloids. Pb speciation and partitioning can be described by geochemical modelling.